The General Statutes of the Commonwealth of Kentucky. To Which are Prefixed Magna Charta, the Constitution of the United States, the Constitutions of Kentucky, and the Other Documents Ordered by Law Page 669 ch. 76 art. V § 3(1873) - (:unkn) unknown (General Publisher, 1873)
A soldier who unnecessarily, or without order from a superior officer, comes to any parade with his musket, rifle, or pistol loaded with ball, slug, or shot, or shall so load the same while on duty, or unnecessarily, or without order from a superior officer, discharges the same when going to, returning from, or upon parade, shall forfeit not less than one nor more than five dollars.
--
Keywords: ARMED FORCES